Practical issues in the management of sleep, anxiety, and mood disorders in primary headaches - Patrick Emanuell Mesquita Sousa-Santos; Mario Fernando Prieto Peres (Arquivos de Neuro-Psiquiatria)
There are many conditions associated with primary headaches, including mood (depression), anxiety, and sleep disorders, which are highly prevalent in the general population and in tertiary headache centers. We call this set of symptoms migraine, anxiety, mood, and sleep (MAMS). The presence of one or more of these symptoms can alter the clinical course and represent a practical challenge. In the present study, we aimed to describe a practical approach to treat these symptoms frequently associated with headaches. Diagnostic aspects and secondary causes were addressed as well as the shared mechanisms and cause and effect relationship. Finally, we commented on the therapeutic approach used to treat these symptoms.